2015
DOI: 10.1016/j.catena.2015.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Temporal stability of surface soil moisture of different vegetation types in the Loess Plateau of China

Abstract: The temporal stability of soil moisture (TSSM) was widely applied to optimize the soil moisture sampling scheme on a catchment or even larger spatial scale over wet and dry observational periods. However, the integration of the TSSM feature with specific hydrological response at a small plot scale has not been sufficiently researched. This study analyzed the temporal stability of surface soil moisture (0-10 cm) characteristics and corresponding influencing factors of different vegetation types under two typica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 59 publications
2
17
0
Order By: Relevance
“…However, multiple land cover combinations disturbed this trend along the slope, and different combinations resulted in fluctuations in the soil moisture content from the lower to upper portion of the slope. Different land use or cover types increase the variability of soil moisture in space and time, but the type of stability of the soil moisture results in a pattern of stability that is often called temporal stability (Zhou et al 2015). It is necessary to measure the temporal stability of the soil moisture content to identify representative locations in this revegetated, typically hilly-gully Loess Plateau catchment.…”
Section: Discussionmentioning
confidence: 99%
“…However, multiple land cover combinations disturbed this trend along the slope, and different combinations resulted in fluctuations in the soil moisture content from the lower to upper portion of the slope. Different land use or cover types increase the variability of soil moisture in space and time, but the type of stability of the soil moisture results in a pattern of stability that is often called temporal stability (Zhou et al 2015). It is necessary to measure the temporal stability of the soil moisture content to identify representative locations in this revegetated, typically hilly-gully Loess Plateau catchment.…”
Section: Discussionmentioning
confidence: 99%
“…Loessial soil, one kind of Calcic Cambisols in the study area is representative of the Loess Plateau. Its specific properties are a uniform texture, high porosity, and high erosivity (Zhou et al 2015). The distribution range of vegetation in the study site was classified as a forest-steppe vegetation area.…”
Section: Site Descriptionmentioning
confidence: 99%
“…Implications for typical re-vegetated hilly and gully loess areas Soil moisture acts as a crucial factor in vegetation production in the Loess Plateau and has garnered a great deal of attentions in recent decades Wang et al 2012Wang et al , 2013Zhou et al 2015). However, manual sampling is difficult and time consuming, making it ill suited for large scale studies.…”
Section: Representative Stability Sites Of the Catchmentmentioning
confidence: 99%
“…The factors that determine SWC depend on the environment of the area of study and the presence or absence of vegetative canopy [14] and the spatio-temporal variability of SWC affect vegetation coverage and density [15]. Investigations on agricultural watersheds have shown that topography, rainfall, and soil texture have mixed effects on SWC at the watershed and regional scales, and that land cover influences runoff, interception and evapotranspiration processes, and in turn, the soil water dynamics [5,[16][17][18][19]. The spatial-temporal pattern of SWC can be obtained from measurements carried out in different experimental plots [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…For investigating the spatio-temporal variability of SWC, both statistical and geostatistical methods have been applied using ground-based and remote sensing data [17,19,24,26]. A few studies have applied the entropy theory to investigate the spatio-temporal variability of SWC and dominant factors [30].…”
Section: Introductionmentioning
confidence: 99%